Mardi and Spenser's wandering allegory. Issue 7 (2nd July 2020) - Hadfield, Andrew
ABSTRACT: In this essay I want to make the case that Edmund Spenser had a crucial impact on Melville's career, one that has been acknowledged – most significantly by Carole Moses – but never fully developed. Melville read, re-read and thought about Spenser over a number of years as the surviving copies of his work attest with their extensive markings. Like his friend Nathaniel Hawthorne, whose mother adapted Spenser for children and who named his daughter, Una, after the heroine of Book I of The Faerie Queene, Melville turned to Spenser when he needed to think about allegory and romance. Furthermore, as Hershel Baker points out in his biography when Melville set down to write Mardi, he was acutely conscious of the change in his status, and he now had proper time to assemble his sources and make use of them. Accordingly he employed Spenser to help him make the work he had completed in Typee and Omoo more literary. In many ways, Melville is too much in thrall to Spenser and fails to escape from his influence, an influence filtered through the image of Spenser as the gothic poet of dreams, ruined castles, dark sexuality, and a landscape hovering between good and evil, beauty and barely hidden ugliness, motifs which are translated to the wandering islands in the south seas. Mardi is, in Bloomian terms, a weak reading that had to be made for the strong misreading which established the writer's identity to follow. Moby Dick has a number of Spenserian references and motifs, but it is not a Spenserian work like its predecessor. In this essay, I want to make the case that the elaborate gothic allegories and complex ornate style of Melville's mature work could only have developed after he worked out how he was to make use of the literary canon he devoured on his sea voyages. Moby Dick may be only intermittently Spenserian in style and substance but it was only possible because of the allegorically Spenserian Mardi, which paved the way for Melville's mature work.